Effects of non-invasive neurostimulation on autism spectrum disorder: A systematic review - Zhang, Jiawei; Zhang, Hao (Frontiers in Psychiatry, 2022)
Non-invasive neurostimulation techniques (NIBS) have shown benefits in psychiatric conditions. While in ASD patients, no guideline has so far recommended these techniques due to a lack of high-quality synthetic evidence. Here, a comprehensive search from database inception onwards was conducted in PubMed, EMBASE, and Cochrane library. Sham-controlled studies assessing the effects of NIBS in ASD patients were identified. After the screening, twenty-two studies were included. A total of 552 patients were involved and the sample size ranged from 5 to 78 patients. Although an iteration from exploratory attempts to more strictly designed trials has been seen to evaluate the efficacy of NIBS on ASD, further trials should also be needed to enable the clinicians and researchers to reach any consensus.